PENGARUH PENGELUARAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP DANA PIHAK KETIGA, JUMLAH PEMBIAYAAN, DAN PROFITABILITAS - Priambodo, Luthfi Azhar; Adityawarman, Adityawarman (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to find out wether the emplementation of CSR in Islamic bank has met the standards and examines the influence of CSR expenditure toward third party fund, loan amount, and profitability.The population in this study consists of all Islamic bank that are and operate in Indonesia in the range of 2014-2017 period. A total sample of 46 companies were used in this study as determined by purposive sampling method. The data used is secondary data. Data analysis was performed with descriptive statistics, classical assumption and hypothesis testing of correlation and regression method using SPSS 23 software.The analysis showed that the implementation of CSR activities by Islamic bank in Indonesia has sufficient and CSR expenditure have positive significant influenced toward third party fund, loan amount, and profitability.